Epistemological and Methodological Elements of the Sociological Discourse Analysis: opening possibilities to the Organizational Studies - Godoi, Christiane Kleinübing; Coelho, Ana Lúcia de Araújo Lima; Serrano, Araceli (Organizações & Sociedade, 2014)
Sociological Discourse Analysis (SDA) linked to the Spanish Tradition of Social Qualitative Research, and one of its choices most common, is not even mentioned, in manuals of qualitative methods and discourse analysis. In organizational studies, the interchange with the discussions of the field of sociology can enable the demystification of discourse analysis to find a methodology concerned not with the internalist textual style, or its underlying structure, but with the performance of this complex phenomenon cognitive and social called discourse. This essay aims to systematize the epistemological and methodological elements of Sociological Discourse Analysis. Is structured in sections: a) analysis of the origins of SDA b) systematization of theoretical and epistemological elements selected as relevant both to understanding the method and its differentiation c) development of methodological elements of ASD, and finally, d) critical alert to the risks of pseudo-analysis in SDA. We intend, therefore, begin defining the space of SDA within the brazilian organizational studies.